REMAJA CERDAS TANPA DRAMA: EDUKASI KESEHATAN REPRODUKSI, MENTAL, DAN GIZI SEIMBANG DI SMA NEGERI 1 SUKA MAKMUR - Fitriyanti Fitriyanti; Rouzatun Nisa; Raudhatun Nuzul ZA (Universitas Ubudiyah Indonesia, 2026)
The adolescent period constitutes a critical and multidimensional developmental stage, characterized by simultaneous transformations across biological, psychological, and social domains, necessitating structured and evidence-based health education responses. This community service program was designed to enhance the knowledge, attitudes, and health literacy of grade XI students at SMA Negeri 1 Suka Makmur across three principal domains: reproductive health, mental health, and balanced nutrition, through the implementation of an integrated, evidence-based educational intervention. The program employed a Participatory Learning and Action (PLA) methodology, integrating multimedia-based interactive lectures, Focus Group Discussions (FGD), case simulations, and structured educational games. The program was conducted over two days in March 2026, involving 120 student participants. Program effectiveness was assessed using validated pre-test and post-test questionnaire instruments. Data analysis revealed statistically significant improvements in mean knowledge scores across all domains: reproductive health increased from 58.4 to 82.1 (delta 40.6%), mental health from 55.7 to 79.8 (delta 43.3%), and balanced nutrition from 61.2 to 83.6 (delta 36.6%). Furthermore, 91.7% of participants reported high levels of satisfaction with the overall program. These findings consistently demonstrate that integrated and participatory health education interventions constitute an effective strategy for holistically improving adolescent health literacy. Accordingly, replication and institutionalization of similar programs within school settings are strongly recommended as a component of national health education policy. Keywords: Adolescent Reproductive Health, Mental Health, Balanced Nutrition, Health Education, Senior High School